Creating Community-Led and Self-Build Homes: A Guide to Collaborative Practice in the UK - Field, Martin (Bristol University Press, 2020)
In Creating Community-Led and Self-Build Homes, Martin Field explores the ways in which people and communities across the UK have been striving to create the homes and neighbourhood communities they want. Giving context to contemporary practices in the UK, the book examines ‘self-build housing’ and ‘community-led housing’, discussing the commonalities and distinctions between these in practice, and what could be learned from other initiatives across Europe. Looking at both individual methods and ‘models’ of local practice, including cohousing, co-operatives, community land trusts, empty homes and other ‘intentional communities’, the book examines what has constrained such initiatives to date and how future policies and practice might be shaped.In Creating Community-Led and Self-Build Homes, Martin Field explores the ways in which people and communities across the UK have been striving to create the homes and neighbourhood communities they want. Giving context to contemporary practices in the UK, the book examines ‘self-build housing’ and ‘community-led housing’, discussing the commonalities and distinctions between these in practice, and what could be learned from other initiatives across Europe. Looking at both individual methods and ‘models’ of local practice, including cohousing, co-operatives, community land trusts, empty homes and other ‘intentional communities’, the book examines what has constrained such initiatives to date and how future policies and practice might be shaped.